2019
DOI: 10.22159/ajpcr.2019.v12i3.30459
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Knowledge, Attitudes, and Practices on Uncomplicated Malaria Management in Plateau State, North-Central Nigeria

Abstract: Objectives: This study aimed to assess patients’ knowledge, attitudes, and practices (KAP) on uncomplicated malaria management in primary health-care (PHC) facilities of Plateau state, Nigeria. Methods: A validated self-reported scale known as patients’ KAP instrument for uncomplicated malaria with Cronbach’s alpha reliability of 0.74 was administered to 956 patients that consented to participate in the study across 24 PHC facilities in the state between May and July 2017. The collated data were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Similar to the findings of this study, the study by Munajat et al conducted among Indigenous population in Kelantan showed almost half of the participants had adequate knowledge on the causes and symptoms of malaria [15]. Similarly, the results were comparable with other international studies which show good knowledge, attitude and practice towards the prevention of malaria [26,27,[31][32][33]. Again, these findings suggest the attention given to Malaria has reaped positive outcomes, however the rates of malaria reduction are not equally seen in developing countries worldwide.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the findings of this study, the study by Munajat et al conducted among Indigenous population in Kelantan showed almost half of the participants had adequate knowledge on the causes and symptoms of malaria [15]. Similarly, the results were comparable with other international studies which show good knowledge, attitude and practice towards the prevention of malaria [26,27,[31][32][33]. Again, these findings suggest the attention given to Malaria has reaped positive outcomes, however the rates of malaria reduction are not equally seen in developing countries worldwide.…”
Section: Discussionsupporting
confidence: 90%
“…The descriptive statistics test for healthcare workers and patients had been reported [17, 18]. Tests for statistically significant differences and relationships for respondents' KAP on uncomplicated malaria management across their independent variables were conducted through inferential statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Data for this study were from two sources titled ‘patients' knowledge, attitudes and practices (KAP) on uncomplicated malaria management in Plateau state, north-central Nigeria’ [17] and ‘assessment of primary healthcare workers' knowledge, attitudes, and practices on uncomplicated malaria management in Plateau state, Nigeria’ [18]. Besides logistic preference and the availability of a residing researcher, the disease prevalence justified the choice of Plateau state as the study area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents that answered between 8 and 10 items correctly had scores of between 8 and 10, and were categorised as having good knowledge, while those that got between 5 and 7 items right were allocated score of between 5 and 7 points, and were considered to have moderate knowledge. Similarly, those who got less than 5 of the items correctly had total scores of between less than 5 and were categorised as having a poor knowledge on uncomplicated malaria and its management (Jimam and Ismail, 2019). Treatment seeking behaviour of respondents was categorised as good, moderate, or poor as described by Ugo et al (2016): i.…”
Section: Discussionmentioning
confidence: 99%